Release profile and characteristics of electrosprayed particles for oral delivery of a practically insoluble drug. - Bohr, A; Kristensen, J; Dyas, M; Edirisinghe, M; Stride, E (2012)
Poly(lactic-co-glycolic acid) (PLGA) microspheres containing celecoxib were prepared via electrospraying, and the influence of three processing parameters namely flow rate, solute concentration and drug loading, on the physico-chemical properties of the particles and the drug-release profile was studied. Microspheres with diameters between 2 and 8 μm were produced and a near-monodisperse size distribution was achieved (polydispersivity indices of 6-12%). Further, the inner structure of the particles showed that the internal porosity of the particles increased with increasing solvent concentration. X-ray powder diffraction (XRPD) analysis indicated that the drug was amorphous and remained stable after eight months of storage. Drug release was studied in USP 2 (United States Pharmacopeia Dissolution Apparatus 2) dissolution chambers, and differences in release profiles were observed depending on the parametric values. Changes in release rate were found to be directly related to the influence of the studied parameters on particle size and porosity. The results indicate that electrospraying is an attractive technique for producing drug-loaded microspheres that can be tailored towards an intended drug-delivery application. Compared with the more conventional spray-drying process, it provides better control of particle characteristics and less aggregation during particle formation. In particular, this study demonstrated its suitability for preparing capsules in which the drug is molecularly dispersed and released in a sustained manner to facilitate improved bioavailability.